PERAN INDIKATOR KEKAYAAN INTELEKTUAL TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Puspitasari, Elen; Srimindarti, Ceacilia (Proceeding Fakultas Ekonomi, 2013)
Capability of knowledge and technology becomes a key factor for the progress of the economy in many developed countries, so there is a necessity intended for companies to change their business strategy, which was originally based labor force towards knowledge-based businesses. Companies need to communicate some other information to users of financial statements related to the value added that is owned by the company i.e. intellectual capital (IC).This study will describe the role of IC indicators as measured by VAICTM, which consists of VACA, VAHU, and STVA to the companys performance measured by market valuation, profitability and productivity,which firm size as a control variable. The population in this study is manufacturing companies listed on the IDX from 2007 to 2010, with purposive sampling to obtain a sample of 20 companies with 80 data observations. The results of statistical hypothesis testing using multiple linear regression test showed that the IC has a positive and significant influence on companys performance.Keywords: Intellectual Capital, Value Added, Performance.